2020
DOI: 10.7759/cureus.9372
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation of the Greek Versions of the Lysholm Knee Scoring Scale and Tegner Activity Scale

Abstract: The Lysholm Knee Scoring Scale (LKSS) and the Tegner Activity Scale (TAS) are widely used instruments for assessing knee function and activity level in various knee pathologies, especially knee ligament injuries. The purpose of this study was to translate and crossculturally adapt the Greek versions of the Lysholm Knee Scoring Scale (Gr-LKSS) and Tegner Activity Scale (Gr-TAS) and assess their reliability and validity in Greek patients suffering from various knee problems. Materials and methods Translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
5
14
0
Order By: Relevance
“…The reliability of the TAS-Ar is also similar to that of the previous adaptation of the scale into Dutch (ICC = 0.97) [11] and Simplified-Chinese (ICC = 0.99) [10] in patients post-ACLR. Furthermore, our results are comparable to the results of the Persian version in patients with ACL injury (ICC = 0.81) [12] and the Greek version in patients with ACL and other knee injuries (ICC = 0.87) [13]. In our study, patients who completed the TAS-Ar for test-retest reliability reported no changes in knee function, no recurrent knee injury, and no other injury in any part of the body between the two testing sessions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The reliability of the TAS-Ar is also similar to that of the previous adaptation of the scale into Dutch (ICC = 0.97) [11] and Simplified-Chinese (ICC = 0.99) [10] in patients post-ACLR. Furthermore, our results are comparable to the results of the Persian version in patients with ACL injury (ICC = 0.81) [12] and the Greek version in patients with ACL and other knee injuries (ICC = 0.87) [13]. In our study, patients who completed the TAS-Ar for test-retest reliability reported no changes in knee function, no recurrent knee injury, and no other injury in any part of the body between the two testing sessions.…”
Section: Discussionsupporting
confidence: 83%
“…TAS is one of the most frequently used scales in ACL-related studies to document the level of work/sport activities of patients with ACL injury and ACLR [ 4 , 7 , 8 , 9 ]. Moreover, the TAS has been translated and cross-culturally adapted into different languages [ 10 , 11 , 12 , 13 , 14 ]. To our knowledge, there is a lack of reliable and valid Arabic outcome measures that can be used to evaluate the level of work/sport activities in patients after ACLR.…”
Section: Introductionmentioning
confidence: 99%
“…Six instruments were retrieved that can be used for various knee pathologies, the Knee Outcome Survey-Activities of Daily Living Scale (KOS-ADLS), 12 the Knee Injury and Osteoarthritis Outcome Score (KOOS) 13 and KOOS-Child, 14 the International Knee Documentation Committee Subjective Knee Form (IKDC) 15 , the Lysholm Knee Scoring Scale (LKSS), 16 and the Tegner Activity Scale (TAS). 16 …”
Section: Resultsmentioning
confidence: 99%
“…3 It is usually assessed with factor analysis. In the majority of the studies, factor analysis was not performed, 8 , 11 , 14 , 15 , 16 19 , 20 , 24 , 26 28 , 31 – 33 , 36 and the authors assumed models from other studies that evaluated the structural validity of the construct of interest.…”
Section: Discussionmentioning
confidence: 99%
“…It included 8 domains that assess instability (0–25 points), pain (0–25 points), locking (0–15 points), stair-climbing (0–10 points), swelling (0–10 points), and support (0–5 points), squatting (0–5 points), and limping (0–5 points). The score ranges from 0 to 100 points is calculated, with excellent (95–100 points), good (84–94 points), fair (65–83 points), and poor (≤64 points) (Panagopoulos et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%